Neonatal acute respiratory distress syndrome: a less explored diagnosis - Kumar, Chanchal; Pothala, Rajeev; Bathina, Sushma Poornima; Dodda, Deepika; Rao, Eswara S. (International Journal of Contemporary Pediatrics, 2022)
Neonatal acute respiratory distress syndrome (ARDS) is less explored and unclassified entity although the neonatologists are aware of the existence of this condition. Extensive lung inflammation and surfactant catabolism leading to lung dysfunction are the pathophysiological characteristics of neonatal ARDS which is like in older children and adults. Montreux definition should be used for neonates from birth until 4 weeks or 44 weeks post-menstrual age if born before 40-weeks’ gestation. Trials on surfactant for ARDS in neonates have been performed well before the NARDS definitions and yielded conflicting results. Authors reported a preterm baby identified with neonatal ARDS secondary to polymicrobial sepsis (Candida parasilosis and Coagulase negative Staphylococcus) after meeting the Montreux definition for neonatal ARDS. He was initially treated with conventional ventilation and was successfully treated with high frequency ventilation and surfactant administration. Well-designed preclinical and explanatory clinical studies to investigate the use of surfactant for neonatal ARDS are needed.